2014
DOI: 10.1371/journal.pone.0102913
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Relationships in Macadamia integrifolia Seed Coats – Fundamentals of the Hierarchical Microstructure

Abstract: The shells/coats of nuts and seeds are often very hard to crack. This is particularly the case with Macadamia seed coats, known to exhibit astoundingly high strength and toughness. We performed an extensive materials science characterization of the complex hierarchical structure of these coats, using light and scanning electron microscopy in 2D as well as microCT for 3D characterization. We differentiate nine hierarchical levels that characterize the structure ranging from the whole fruit on the macroscopic sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 20 publications
(54 reference statements)
1
69
0
Order By: Relevance
“…Petrechen [8], incorporated Brazil nut mesocarp particles (NLF) with different polypropylene (PP) matrices and the biocomposites obtained showed significant improvements in several mechanical properties, compared with the PP matrix and with other similar particulate NLF biocomposites [24]. In that way, as already stated for the case of Macadamia seed shell [22,25,26], the Brazil nut fruit mesocarp, due its outstanding mechanical characteristics, could well serve as NFL for biocomposites, or as a hierarchical architecture model for biomimetics materials.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Petrechen [8], incorporated Brazil nut mesocarp particles (NLF) with different polypropylene (PP) matrices and the biocomposites obtained showed significant improvements in several mechanical properties, compared with the PP matrix and with other similar particulate NLF biocomposites [24]. In that way, as already stated for the case of Macadamia seed shell [22,25,26], the Brazil nut fruit mesocarp, due its outstanding mechanical characteristics, could well serve as NFL for biocomposites, or as a hierarchical architecture model for biomimetics materials.…”
Section: Resultsmentioning
confidence: 85%
“…Schüler et al [22] compared the crack resistance of different nuts shells/coats and found a much higher strength for the Macadamia (Macadamia integrifolia) seed coat. Unlike others nuts shells/coats, formed by compact arrangements of sclereid cells [23], the cell arrangement found in the Macadamia seed coat was similar as the found in the Brazil nut fruit mesocarp, where fiber cell bundles and sclereids are acting together as a composite structure, as shown in the Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The tracheid cells are usually surrounded by fibers, that provide mechanical stability to the structure. This kind of cell is common among other nutshells, like in macadamia and coconut 12,13 . Phloem cells are responsible for transporting nutrients through the plant and are formed by sieve elements, as shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…However, an interesting feature in the mesocarp of Brazil nut is how the sclereids are arranged, filling the gaps between the fiber bundles 1 . This arrangement is uncommon in other nutshells such as macadamia 12 , coconut 25 and babassu 22 , where fibers and sclereids are present in different layers of the structure. The cell arrangement in the Brazil nut mesocarp reminds of a foam-filled sandwich structure, as used in the aerospace industry where there is a skin made of a stiff material and the core is filled with foam 16 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation